Chemistry and Biological Activity of Steroids - António Ribeiro Salvador, Jorge; Manuel Cruz Silva, Maria (IntechOpen, 2020)
The steroid scaffold continues to be the structural basis of new drugs for a variety of targets and diseases. Indeed, steroids interact with enzymes and receptors in a strikingly specific manner. Chemistry and Biological Activity of Steroids aims to provide an updated overview of recent advances in the medicinal chemistry of steroids. Novel synthetic methods in the steroids field, including steroid biotransformations, new steroids able to tackle steroid receptors, and steroid enzymes with clinical relevance, are critically reviewed in this book. Furthermore, the diverse physiopathological roles of oxysterols and their therapeutic value are also discussed.